RESEARCH OF THE METHODS OF ASSESSING THE RELIABILITY OF THE MACHINE-BUILDING ENTERPRISE’S LOGISTICS SYSTEM - MASLAK, OLGA; NIKITIUK, VITALII (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The value of the logistics approach to management lies in the integration into a single chain of procurement, storage, production, transportation and marketing of finished products, namely the logistics system creation. The purpose of scientific research is to substantiate the essence of the reliability of the logistics system of the machine-building enterprise and to develop methods for its evaluation. The definitions "reliability of the logistics chain" and "reliability of the logistics system of the machine-building enterprise" are investigated and the terminology of the given definitions is generalized. Factors influencing the reliability of the logistics chain, namely: economic, organizational, technological and physical. A method for assessing the reliability of the logistics chain and logistics system of a machine-building enterprise is proposed. The components of reliability of the logistics system of the machine-building enterprise are formed - purchase of raw materials, storage of material resources, stock management, production of finished products, transportation, sale of finished products. The indicators which are a part of reliability of logistic system of the machine-building enterprise are offered. The essence of management of reliability of logistic system of the machine - building enterprise is defined and its algorithm is constructed. The most common methods of increasing the reliability of supply chains (logistics systems) are systematized. Measures to improve the reliability of the logistics system of the machine-building enterprise are presented. The reliability of the logistics system of a machine-building enterprise is an indicator of the ability of the system to maintain its properties at a given level for a certain period of time under established operating conditions. To increase the reliability of the logistics system of the machine-building enterprise, it is necessary to identify "weak" links in the system that require identification of reserves and their use, which will increase the logistics system reliability of the machine-building enterprise as a whole.